2014
DOI: 10.1021/jp412402v
|View full text |Cite
|
Sign up to set email alerts
|

Dye Self-Association Identified by Intermolecular Couplings between Vibrational Modes As Revealed by Infrared Spectroscopy, and Implications for Electron Injection

Abstract: In this Article, we investigate the effects of binding geometry and intermolecular interactions in monolayers of a rhenium-based dye adsorbed to TiO 2 . We combine two-dimensional infrared (2D IR) spectroscopy of samples prepared with different dye loadings with density functional theory (DFT) calculations of dye binding energies and vibrational frequencies. Our 2D IR spectra reveal splitting of the CO symmetric stretch mode into two peaks of unequal intensity at high surface coverages, which persists even whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(101 citation statements)
references
References 53 publications
(79 reference statements)
6
94
1
Order By: Relevance
“…The Re-based dyes with various bridge lengths are shown in Figure 1a, and the different carboxylic acid binding motifs that we consider are shown in Figure 1b-f. These are the same binding motifs that we considered previously 35 and are analogous to the most stable binding modes of formic acid to anatase. 29 Significant increases in the lifetime broadening (LB) of the dye LUMO, indicative of stronger dye-surface electronic coupling, occur with decreasing bridge length (Table 1).…”
Section: Resultssupporting
confidence: 67%
“…The Re-based dyes with various bridge lengths are shown in Figure 1a, and the different carboxylic acid binding motifs that we consider are shown in Figure 1b-f. These are the same binding motifs that we considered previously 35 and are analogous to the most stable binding modes of formic acid to anatase. 29 Significant increases in the lifetime broadening (LB) of the dye LUMO, indicative of stronger dye-surface electronic coupling, occur with decreasing bridge length (Table 1).…”
Section: Resultssupporting
confidence: 67%
“…These studies demonstrated the usefulness of multi-dimensional spectroscopy regarding the resolution of intermolecular interactions, 17,24 vibrational dephasing and relaxation, as well as spectral diffusion from samples at interfaces. 16,19,49 For instance, variations in spectral diffusion and vibrational relaxation dynamics have been discussed between octahedral rheniumcarbonyl photocatalysts at silica interfaces and in bulk solution, 16,49 revealing that spectral diffusion at surfaces is slower than in bulk solution.…”
Section: General Context Of Spectral Diffusion At Interfacesmentioning
confidence: 82%
“…Multi-dimensional signals from monolayer-forming samples have been reported previously obtained in transmission 2D IR 17,49,60 or with 2D SFG 24,27 spectroscopy. These studies demonstrated the usefulness of multi-dimensional spectroscopy regarding the resolution of intermolecular interactions, 17,24 vibrational dephasing and relaxation, as well as spectral diffusion from samples at interfaces.…”
Section: General Context Of Spectral Diffusion At Interfacesmentioning
confidence: 83%
See 2 more Smart Citations